Translating MSC Therapy in the Age of Obesity - Boland, Lauren; Bitterlich, Laura Melanie; Hogan, Andrew E.; Ankrum, James A.; English, Karen (Frontiers in Immunology, 2022)
Mesenchymal stromal cell (MSC) therapy has seen increased attention as a possible option to treat a number of inflammatory conditions including COVID-19 acute respiratory distress syndrome (ARDS). As rates of obesity and metabolic disease continue to rise worldwide, increasing proportions of patients treated with MSC therapy will be living with obesity. The obese environment poses critical challenges for immunomodulatory therapies that should be accounted for during development and testing of MSCs. In this review, we look to cancer immunotherapy as a model for the challenges MSCs may face in obese environments. We then outline current evidence that obesity alters MSC immunomodulatory function, drastically modifies the host immune system, and therefore reshapes interactions between MSCs and immune cells. Finally, we argue that obese environments may alter essential features of allogeneic MSCs and offer potential strategies for licensing of MSCs to enhance their efficacy in the obese microenvironment. Our aim is to combine insights from basic research in MSC biology and clinical trials to inform new strategies to ensure MSC therapy is effective for a broad range of patients.